A multicentred phase III comparatiye study between single-implant containing 3-ketodesogestrel (Implanon®) and implants containing levonorgestrel (Norplant®) I. Eff¯cacy, acceptability and safety (three-year results) (Faculty of Medicine Universitas Indonesia, 1999)
[no abstract available]